مقرر النحو العربي في المدارس الثانوية الحكومية في الصومال: ‎دراسة وصفية تقويمية - عبدالرحمن، أحمد محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study is conducted to examine the Arabic text books in Somali government secondary schools. The study illustrates different historical stages of teaching Arabic language in Somali government Arabic schools and the challenges they faced. This study aims to identify the difficulties and problems related to the curriculum and its components and the researcher used the analytical descriptive method. One of the most important tools adopted in the research is the questionnaire directed to teachers and students. In addition, the researcher used the descriptive statistical analysis to evaluate the nine axes of the questionnaire. The researcher also analyzed the hypotheses to show the relationship between the independent variable and the dependent variable using the SPSS. Among the most important findings of this study is that the current curriculum and its components are not suitable for Somali students. The Arabic grammar curriculum does not contain any evaluation and development in advance; based on to the needs of the Somali society, the school reality is not encouraging in teaching Arabic grammar course, and the textbook and teachers are not available in most of the Arabic language schools in Somalia. The Arabic teachers have not received sufficient training both inside and outside the country, all of which lead to the weakness of the students and their lack of skills in speaking, reading, and writing in Arabic language.